Забезпечення послуг IoT 5G - Сабурова, С. О.; Сушко, Ю. В. (ХНУРЕ, 2019)
Communication network "fifth generation", the so-called. 5G, along with big data analysis (Big Data) and the Internet of Things (IoT) are intended to become one of the foundations of the digital economy, the main driving force of which should be artificial intelligence (AI). Over 40 years, four generations of mobile networks have changed. If the first-generation 1G cellular networks have disappeared long ago, then 2G, 3G and 4G networks still continue to be used. Moreover, a certain amount of the inherited infrastructure of 3G and 4G networks will organically become part of the fifth-generation 5G mobile networks.
Keywords: IoT; 5G; AI; fifth generation; RFID; mobile network